2007
DOI: 10.1111/j.1365-2427.2007.01753.x
|View full text |Cite
|
Sign up to set email alerts
|

Experimental assessment of the fecundity of Eucypris virens (Ostracoda, Crustacea) under natural sex ratios

Abstract: 1. The adaptive significance of the observed variations in sex ratios in non-marine ostracods is unclear. This study quantified the fecundity of females taken from a presumed fully sexual Eucypris virens population that were experimentally combined with different proportions of males (male : female sex ratios: 1 : 1, 1 : 2, 1 : 4, 1 : 8 and 0 : 1). 2. The results yielded no indications that female fecundity is altered by short-term variations in the proportion of males, at least not within the range of sex rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 19 publications
1
11
0
Order By: Relevance
“…A similar phenomenon was described in sexual lineages of E. virens and H. incongruens (Vandekerkhove et al, 2007;Rossi and Menozzi, 2012b). We suggest that female biased sex ratio, by reducing mating opportunity may affect egg to adult survival and that a difference in sex ratio between hatchlings from resting and non resting eggs may affect H. barbara voltinism and hence its population growth.…”
Section: Discussionmentioning
confidence: 63%
“…A similar phenomenon was described in sexual lineages of E. virens and H. incongruens (Vandekerkhove et al, 2007;Rossi and Menozzi, 2012b). We suggest that female biased sex ratio, by reducing mating opportunity may affect egg to adult survival and that a difference in sex ratio between hatchlings from resting and non resting eggs may affect H. barbara voltinism and hence its population growth.…”
Section: Discussionmentioning
confidence: 63%
“…Although the species is typically regarded as univoltine, a second hatching period is possible (Meisch, 2000). Hatching rates are highly variable among populations and lineages, and depend on the prevailing environmental conditions (Otero et al, 1998;Vandekerkhove et al, 2007;Martins et al, 2008). Adult sexual and asexual E. virens can lay two types of eggs: subitaneous (immediate hatching) and diapausing eggs (desiccation-resistant resting eggs).…”
Section: Study Speciesmentioning
confidence: 99%
“…This last possibility has been discussed for Ostracoda (Abe, 1990;Cohen & Morin, 1990). Differential mother investment in male or female offspring is also possible (see Fisher, 1930;Godfray & Werren, 1996), but there are no indications for this in E. virens based on laboratory experiments ( Vandekerkhove et al, 2007;Martins et al, 2008). If we assume this population is of mixed reproductive mode, sex ratio changes can be explained by a difference in the hatching response of sexual and asexual resting eggs, or by a differential survival of sexuals and asexuals.…”
Section: Eucypris Virens: Population Structure and Dynamicsmentioning
confidence: 99%
“…However, an immediate hatching response may lead to dramatic losses in case the inundation period is too short for reproduction (Martins et al, 2009). Previous studies have shown that inundation of ostracod eggs is sufficient to trigger a hatching response, irrespective of the prevailing temperature and light conditions (Otero et al, 1998;Vandekerkhove et al, 2007;Martins et al, 2008). By relying on a single proximate hatching stimulus, in this case the presence of water, the risk for erratic hatching events is high.…”
Section: Hydrationmentioning
confidence: 99%